Relaxor behavior and electrothermal properties of Sn- and Nb-modified (Ba, Ca)TiO3 Pb-free ferroelectric. Issue 8 (28th April 2020) - Venkateshwarlu, Sarangi; Nayak, Sanjib; Marlton, Frederick P.; Weyland, Florian; Novak, Nikola; Maurya, Deepam; Veerabhadraiah, Yashaswini; Borkiewicz, Olaf; Beyer, Kevin A.; Jørgensen, Mads R.V.; Pramanick, Abhijit
Abstract: Abstract : Relaxor ferroelectrics have drawn attention for possible applications in solid-state cooling and thermal energy harvesting, owing to their electrothermal energy conversion properties. Here, we have synthesized and characterized the structure–property correlations of a new Sn- and Nb-doped (Ba, Ca)TiO3 relaxor ferroelectric with large pyroelectric and electrocaloric effects over a broad temperature range. We observed two peaks for the temperature-dependent pyroelectric coefficient: (i) -(∂ P /∂ T ) ∼ 563 μC/(m 2 K) at T ∼ 270 K and (ii) -(∂ P /∂ T ) ∼ 1021 μC/(m 2 K) at T ∼ 320 K. In addition, a broad peak for electrocaloric temperature change is observed near 320 K with a relative cooling power of ∼ 17 J/kg. These properties could be correlated to structural changes observed using X-ray diffraction at two different temperature ranges in the material. Analysis of high-energy X-ray scattering and specific heat capacity data revealed a transition from the cubic to tetragonal phase near T m ∼ 320 K, whereas an additional increase in the tetragonality ( c / a ) of the polar phase is observed below T s ∼ 270 K.